Pembuatan Jobsheet Praktik Instalasi Penerangan Listrik di Sekolah Menengah Kejuruan - Zuryati Permani; Hambali Hambali (Jurnal Pendidikan Teknik Elektro, 2022)
The subject of Electrical Lighting Installation is one of the subjects taught in class XI and XII TITL at SMK Negeri 1 Rao Selatan. Electrical Lighting Installation subjects consist of two learning activities, namely theory and practice. In the learning process of Electrical Lighting Installation Practice at SMK Negeri 1 Rao Selatan, problems were found in the form of unavailability of teaching materials (jobsheets) for class XI TITL students. In the learning process of the Electric Lighting Installation Practice, the teacher still uses the lecture method using the whiteboard media to explain the circuit drawing to be worked on, causing the practical learning process to be less effective. This study aims to produce a valid, practical and effective jobsheet on the subject of Electrical Lighting Installation class XI TITL at SMK Negeri 1 Rao Selatan. This type of research is Research & Development (R&D) using a 4D development model consisting of four stages, namely Define, Design, Develop, and Desiminate. Data collection was carried out using three instruments, namely a validation questionnaire, a practicality questionnaire, and a work assessment sheet (rubric). Based on the results of the jobsheet validity test by three validators, the jobsheet is stated in the very valid category. The results of the practicality test by teachers and students on the worksheets are stated in the practical category. The results of the effectiveness test, the worksheet was declared to be effectively used. The conclusion of this research is that the jobsheet is valid, practical and effective to use in the practical learning of Electrical Lighting Installation for class XI TITL at SMK Negeri 1 Rao Selatan.